EFFECTIVENESS OF BENSON RELAXATION TECHNIQUE ON PAIN INTENSITY IN POST SECTIO CAESAREA PATIENTS AT SELARAS HOSPITAL TANGERANG IN 2023 - Mustafa, Ayu Resky; Anisa, Pipilia (HEARTY, 2025)
Background: Sectio Caesarea has side effects, including that the first few days after delivery will cause severe pain in the incision area, caused by tearing of the tissue in the abdominal wall and uterine wall, the levels of which are different for each mother. Pain after Sectio Caesarea surgery can occur. overcome with various new techniques that have been developed, such as a non-pharmacological approach, namely the Benson relaxation technique. Objective: To determine the effectiveness of the Benson relaxation technique on pain intensity in post caesarean section patients at Selaras Hospital Tangerang in 2023. Method: Quantitative research using a quasi-experimental design with a one group pre-post test design approach. The sampling technique used a total sampling technique so that the number of samples in this study was 30 respondents. The research instruments included questionnaires, checklists, interview guide questionnaires, observation guidelines, laboratory examination tools and used the Wilcoxon test. Results: There is an effect of the effectiveness of the Benson relaxation technique on pain intensity in Post Sectio Caesarea patients with a significance value of <0.05, namely 0.000 at Selaras Hospital Tangerang in 2023. Conclusion: It is hoped that this research can be applied to pain management using the Benson relaxation technique as an effort to relieve post-Section Caesarea pain in oneself, family and relatives.